fNIRS neuroimaging in olfactory research: A systematic literature review - Gunasekara, Natalie; Gaeta, Giuliano; Levy, Andrew; Boot, Eleanor; Tachtsidis, Ilias (Frontiers in Behavioral Neuroscience, 2022)
There are a number of key features which make olfaction difficult to study; highly diverse odour feature space, subjective processes of odour detection, discrimination and identification, and individualistic odour hedonic perception and associated odour memories. In this systematic review we explore the role fNIRS has played in understanding olfactory perception in humans. fNIRS is an optical neuroimaging technique able to measure changes in brain hemodynamics and oxygenation related to neural electrical activity. Normal adult healthy populations were used, with some clinical studies observing autism, ADHD, PTSD, mild cognitive impairment (MCI), dysosmia and covid-19 related cases. fNIRS coverage heavily favoured the prefrontal cortex in particular, as well as temporal and parietal regions. This review finds that odour induced cortical activation is dependent on multiple factors, such as odourant type, gender and population type. Generally, the majority of studies involving healthy adult subjects observed increased activity in response to odours.